Anti-apoptotic and anti-fibrotic efficacy of exercise training in hypertensive hearts: A systematic review - Akbar, Adjar Yusrandi; Cui, Zhen-Yang; Hsu, Che-Jui; Li, Yan-Zhang; Rahman, Ferry Fadzlul; Xia, Chunqiu; Yang, Ai-Lun; Lee, Shin-Da (Frontiers in Cardiovascular Medicine, 2023)
Background: This review aimed to summarize the ant-apoptotic, pro-survival, and anti-fibrotic effects of exercise training in hypertensive hearts. Methods: Keyword searches were conducted through May 2021 in PubMed, Web of Science, and Scopus. The researches published in English on the effects of exercise training on apoptosis pathway, survival pathway and fibrosis pathway in hypertension were included. The CAMARADES checklist was used to determine the quality of the studies. Two assessors independently carried out the pre-designed protocols for searching and selecting studies, assessing study quality, and evaluating evidence strength. Results: Eleven studies were included after selection. The duration of the exercise training ranged between 5-27 weeks. Nine studies showed that exercise training improved cardiac survival by increasing IGF1, IGF1 receptor, p-PI3K, Bcl-2, HSP 72, and p-Akt. Furthermore, ten studies showed that exercise training reduced apoptotic pathways by downregulating Bid, t-Bid, Bad, Bak, Bax, TNF, and FADD. Lastly, two studies reported the repair of the physiological characteristic of fibrosis and the decreased MAPK p38 and PTEN level by exercise training in the heart’s left ventricle. Conclusion: The review findings showed that exercise training could enhance cardiac survival and attenuate cardiac apoptotic and fibrotic pathways in hypertension, suggesting that exercise training could act as a therapeutic approach to prevent hypertension-induced cardiac apoptosis and fibrosis. PROSPERO registration ID: CRD42021254118